Patrones de diversidad de hormigas en el bosque nublado de la Reserva Arcoiris y la Reserva el Madrigal Ecuador - Piedra Campoverde, Gabriela Beatriz (2015)
Richness, abundance and functional groups of ants from cloud forests of the Madrigal Ecological Reserve, 2350m, and the Arcoiris Ecological Reserve, 2100m, were determined by sifting leaf litter, placing pitfall traps, washing soil and manual collecting. Ninteen species of ants from 15 genera were collected with Myrmicinae as the most species and genera rich group, followed by Ponerinae. The estimators ICE, Chao2 and Jacknife 2 assessed collection completeness as 91.2% for Arcoiris and 63.1% for El Madrigal. Shannon's proportional equity abundance shows median diversity for both sites whilst Simpson's proportional dominance abundance shows low species dominance form both sites. The most frequent genus in both sites is Pheidole, but the most frequent species of all is Hypoponera trigona (Arcoiris). In Arcoiris and El Madrigal 11 and 12 species of ants were respectively collected, of which 4 are shared but 79% of the species are found in one site only and 68% are considered rare. Beta diversity was compared using the Sørensen similarity coefficient and the complementarity coefficient, showing quite different faunas amongst the sites. The ants were classified into functional groups, with the most common being nomadic hunters in El Madrigal and cryptic omnivores in Arcoris. Notable species are: Simopelta manni, found for the first time since the 1930s; Myrmelachista zeledoni, registered for the country for the first time; Neivamyrmex macrodentata is found in South America for the first time; and the following new species are found: Strumigenys lojanensis, Strumigenys madrigalae, and Protalaridris n. sp.